Enhancing Sales through Marketing Strategy and Customer Satisfaction in Culinary MSMEs: Meningkatkan Penjualan melalui Strategi Pemasaran dan Kepuasan Pelanggan pada UMKM Kuliner - Arista, Sintha Wahyu; Fitriyah, Hadiah (Indonesian Journal of Law and Economics Review, 2024)
This quantitative study investigates the impact of marketing strategy and consumer satisfaction on sales growth in Micro, Small, and Medium Enterprises (MSMEs) within the culinary sector of Krembung District, Sidoarjo Regency. Data collected from 100 MSME owners via questionnaire surveys using Google Forms reveals significant positive effects of both marketing strategy (Tcount = 3.568, p = 0.001) and consumer satisfaction (Tcount = 2.325, p = 0.022) on increasing sales. The findings highlight the critical role of strategic marketing planning and customer satisfaction in enhancing business performance and competitiveness, underscoring the need for MSMEs to prioritize these factors to achieve sustainable growth and profitability in competitive markets. Highlight: Quantitative study on marketing impact in culinary MSMEs. Significant influence of customer satisfaction on sales growth. Practical implications for enhancing business strategies in MSMEs. Keywords: Sales enhancement, marketing strategy, customer satisfaction, MSMEs, culinary sector